Implementation of Data Collection Policy and Tax Information on Directorate General of Taxes - Redhy Matabean; Vishnu Juwono (Jurnal Borneo Administrator, 2021)
The Directorate General of Taxation has the authority to collect data and information related to taxation from agencies, institutions, associations, and other parties (ILAP) through Government Regulation No. 31 of 2012. Data and information collected from the ILAP, including transaction, identity, licensing, and non-transactional data, are used to build tax databases and explore potential taxation. This study aims to analyze the implementation of data and information collected in the context of taxation and investigate the factors that support and inhibit the implementation by using the variable implementation of the hybrid policy model. This work is qualitative research with a post-positivist approach. Data collection was done by conducting in-depth interviews and literature reviews. Data analysis was carried out through data reduction, presentation, conclusions, and verification. The study showed that the implementation of data collection and information related to taxation has helped the Directorate General of Taxation build a tax database and taxpayer profile. However, there are still obstacles, such as the unavailability of an information system to monitor data use and barriers in incomplete data received. The inhibiting factors affecting implementation are the non-target setting of policy objectives and standards, lack of resources, and inadequate communication and coordination. The factors that support the implementation of this policy are the high motivation of policy implementers, the active role of policy implementers, and the adaptability of implementers.